Pharmacokinetic–pharmacodynamic modeling of fostamatinib efficacy on ACR20 to support dose selection in patients with rheumatoid arthritis (RA). (20th November 2014) - Maringwa, John; Kågedal, Matts; Hamrén, Ulrika Wählby; Martin, Paul; Cox, Eugène; Hamrén, Bengt
Abstract R788 (fostamatinib) is an oral prodrug that is rapidly converted into a relatively selective spleen tyrosine kinase (SYK) inhibitor R406, evaluated for the treatment of rheumatoid arthritis (RA). This analysis aimed at developing a pharmacodynamic model for efficacy using pooled ACR20 data from two phase II studies in patients with rheumatoid arthritis (TASKi1 and TASKi2), describing the effect of fostamatinib as a function of fostamatinib exposure (dose, R406 plasma concentration) and other explanatory variables. The exposure–response relationship of fostamatinib was implemented into a continuous time Markov model describing the time course of transition probabilities between the three possible states of ACR20 non‐responder, responder, and dropout at each visit. The probability of transition to the ACR20 response state was linearly (at the rate constant level) related to average R406 plasma concentrations and the onset of this drug effect was fast. Further, increases of fostamatinib dose resulted in increased dropout and subsequent loss of efficacy. This analysis provided an increased understanding of the exposure–response relationship, and provided support for fostamatinib 100 mg BID an appropriate dose regimen for further clinical evaluation.